Monopoli dan persaingan usaha tidak sehat: Antara kebebasan perusaha dan melindungi kepentingan publik - Mubarok, Muhammad Aunul (Maliki Interdisciplinary Journal, 2024)
This paper discusses about monopolies and unhealthy business competition in Indonesia and how competition law can protect public interests. Monopoly is a market structure where there is only one producer dominating the market. Unhealthy business competition occurs when businesses engage in actions that harm competitors and consumers. Competition law is an important legal framework in a market economy to prevent monopolies and unhealthy business competition. However, there are challenges in balancing corporate freedom and protecting public interests. Therefore, effective supervision and law enforcement are necessary to prevent monopolistic practices and unhealthy business competition.